KEANEKARAGAMAN KUPU-KUPU, TUMBUHAN PAKAN LARVA DAN IMAGO DI HUTAN LINDUNG GUNUNG TAMPUSU DAN MAHAWU - Mufti Aldya Rivai; Hard N. Pollo; Jackson F. Watung (Universitas Sam Ratulangi, 2021)
Abstract Butterflies are a group of insects belonging to the order Lepidoptera, which have two pairs of wings and a scaly body. Butterfly species richness may decrease due to increased deforestation and conversion of forest land which affect the diversity of larval and imago feed plants. The purpose of this research was to analyze the diversity of butterfly species and feed plants for larvae and imago in the protected forests of Mount Tampusu and Mahawu. The method used in this research is the pathway count method. The results showed that there were 5 families of 37 species of butterflies in the two research locations including 26 species in the Mount Tampusu protected forest and 23 species in the Mount Mahawu protected forest. The results of the analysis of the Shannon-Wiener diversity index are H'= 2.74 and the evenness index analysis is: E = 2.74/ln (37) = 0.76. The larval food plants found in the Mount Tampusu Protection Forest were Ficus sp. and feed for larvae found in the Mount Mahawu Protection 2 Forest, namely Glochidion sp., and Alpinia sp.. The imago feed plants in the Mount Tampusu Protection Forest were Crassocephalum crepidioides, Lantana camara, Lindernia crustacean, Mikania cordata and forage plants in the Mount Protection Forest, namely Bidens pilosa, Crassocephalum crepidioides, Hyptis capitate, Impatiens sp., Sida acuta, and Vernonia sp.. Keywords: Butterflies, host plant and food plant, Mount Tampusu and Mahawu protected forests